SISTEM PAKAR DIAGNOSIS MESIN PENGERING TEH DI WONOSARI MENGGUNAKAN METODE FORWARD CHAINING - kiswara, Helga Ayuddya; Yunus, Mahmud; Widarti, Dinny Wahyu (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
An expert system was developed in line with the information technology . Development of an expert system is intended as aids to provide solutions in our lives .. This expert system could help technicians in getting solutions quickly and can save time . Expert systems use computer technology to integrate , manipulate and display information or characteristics . Expert systems can also help in making a better solution. With the rapid advancement in technology today, emerged an idea to implement a program of expert system application into a computer technician service quality activities . The author tries to build an application that will help to facilitate in providing solutions damage the dryer Wonosari tea in tea gardens so as to facilitate the user or technician to get a solution quickly sehinnga reduce impact damage diimbulkan by damage to the dryer. The system created is